ETNOMATEMATIKA PADA TARIAN DAYAK TOTOKNG DI SANGGAR SENI NYIUR SINGKAWANG - Melinda, Meisya; Septianawati, Desty (Bahasa Indonesia, 2023)
This study aims to describe how to the math of the Dayak Totokng dance is performed. This research used qualitative and an ethnographic approach. The data that the author generated was by way of observation and documentation. Based on the result of this research the Dayak Totokng dance is a dance to welcome and pay homage to jubata, the form of respect is in the form of their gratitude for the result they get. The result of this study can be applied to class VII junior high school students.